N-acyl-homoserine-lactones signaling as a critical control point for phosphorus entrapment by multi-species microbial aggregates. (1st October 2021) - Xu, Ying; Curtis, Thomas; Dolfing, Jan; Wu, Yonghong; Rittmann, Bruce E.
Highlights: l C8-HSL, 3OC8-HSL and C12-HSL were the primary AHL regulators of P entrapment l Both intra- and extra-cellular P entrapment were enhanced in the addition of AHLs. l AHLs facilitated extra-P entrapment by stimulating EPS biosynthesis l QS enhanced intra-P entrapment via transcriptional regulation of ppk, pit, pstSCAB genes l New conceptual model of regulatory networks for QS signaling on P entrapment was proposed Abstract: Quorum sensing (QS) has been extensively studied in pure stains of microorganisms, but the ecological roles of QS in multi-species microbial aggregates are poorly understood due to the aggregates' heterogeneity and complexity, in particular the phosphorus (P) entrapment, a key aspect of element cycling. Using periphytic biofilm as a microbial-aggregate model, we addressed how QS signaling via N-acyl-homoserine-lactones (AHLs) regulated P entrapment. The most-abundant AHLs detected were C8-HSL, 3OC8-HSL, and C12-HSL, are the primary regulator of P entrapment in the periphytic biofilm. QS signaling-AHL is a beneficial molecule for bacterial growth in periphytic biofilm and the addition of these three AHLs optimized polyphosphate accumulating organisms (PAOs) community. Growth promotion was accompanied by up-regulation of pyrimidine, purine and energy metabolism. Both intra- and extra-cellular P entrapment were enhanced in the addition of AHLs. AHLs increased extracellular polymeric substances (EPS) production to drive extracellular P entrapment, via up-regulating amino acids biosynthesis and amino sugar/nucleotide sugar metabolism. Also, AHLs improved intracellular P entrapment potential by regulating genes involved in inorganic-P accumulation ( ppk, ppx ) and P uptake and transport ( pit, pstSCAB ). This proof-of-concept evidence about how QS signaling regulates P entrapment by microbial aggregates paves the way for managing QS to enhance P removal by microbial aggregates in aquatic environments. Graphical abstract: Image, graphical abstract